Atractylenolide I ameliorates cancer cachexia through inhibiting biogenesis of IL‐6 and tumour‐derived extracellular vesicles. Issue 6 (9th September 2022) - Fan, Meng; Gu, Xiaofan; Zhang, Wanli; Shen, Qiang; Zhang, Ruiqin; Fang, Qiaoyu; Wang, Yueping; Guo, Xiaodong; Zhang, Xiongwen; Liu, Xuan
Abstract: Background: Atractylenolide I (AI) is a natural sesquiterpene lactone isolated from Atractylodes macrocephala Koidz, known as Baizhu in traditional Chinese medicine. AI has been found to ameliorate cancer cachexia in clinic cancer patients and in tumour‐bearing mice. Here, we checked the influence of AI on biogenesis of IL‐6 and extracellular vesicles (EVs) in cancer cachexia mice and then focused on studying mechanisms of AI in inhibiting the production of tumour‐derived EVs, which contribute to the ameliorating effects of AI on cancer cachexia. Methods: C26 tumour‐bearing BALB/c mice were applied as animal model to examine the effects of AI (25 mg/kg) in attenuating cachexia symptoms, serum IL‐6 and EVs levels. IL‐6 and EVs secretion of C26 tumour cells treated with AI (0.31–5 μM) was further observed in vitro. The in vitro cultured C2C12 myotubes and 3T3‐L1 mature adipocytes were used to check the potency of conditioned medium of C26 cells treated with AI (0.625–5 μM) in inducing muscle atrophy and lipolysis. The glycolysis potency of C26 cells under AI (0.31–5 μM) treatment was evaluated by measuring the extracellular acidification rate using Seahorse XFe96 Analyser. Levels of related signal proteins in both in vitro and in vivo experiments were examined using western blotting to study the possible mechanisms. STAT3 overexpression or knockout C26 cells were also used to confirm the effects of AI (5 μM). Results: AI ameliorated cancer cachexia symptoms ( P  < 0.05), improved grip strength ( P  < 0.05) and decreased serum EVs ( P  < 0.05) and IL‐6 ( P  < 0.05) levels of C26 tumour‐bearing mice. AI directly inhibited EVs biogenesis ( P  < 0.001) and IL‐6 secretion ( P  < 0.01) of cultured C26 cells. The potency of C26 medium in inducing C2C12 myotube atrophy (+59.54%, P  < 0.001) and 3T3‐L1 adipocyte lipolysis (+20.73%, P  < 0.05) was significantly attenuated when C26 cells were treated with AI. AI treatment inhibited aerobic glycolysis and the pathway of STAT3/PKM2/SNAP23 in C26 cells. Furthermore, overexpression of STAT3 partly antagonized the effects of AI in suppressing STAT3/PKM2/SNAP23 pathway, EVs secretion, glycolysis and the potency of C26 medium in inducing muscle atrophy and lipolysis, whereas knockout of STAT3 enhanced the inhibitory effect of AI on these values. The inhibition of AI on STAT3/PKM2/SNAP23 pathway was also observed in C26 tumour tissues. Conclusions: AI ameliorates cancer cachexia by decreasing the production of IL‐6 and EVs of tumour cells. The decreasing effects of AI on EVs biogenesis are based on its inhibition on STAT3/PKM2/SNAP23 pathway.